2020
DOI: 10.3390/nu12082269
|View full text |Cite
|
Sign up to set email alerts
|

Impaired CPT1A Gene Expression Response to Retinoic Acid Treatment in Human PBMC as Predictor of Metabolic Risk

Abstract: Ex vivo human peripheral blood mononuclear cell (PBMC) systems offer the possibility to test transcriptomic effects of food bioactive compounds with potential health effects. We investigated all-trans retinoic acid (ATRA) effect on mRNA expression of key lipid metabolism and inflammatory genes in PBMCs from normal-weight (NW) and overweight-obese (OW-OB) men with different metabolic syndrome-related features. PBMCs were incubated with 10 µM ATRA and mRNA levels of selected genes were analyzed using real-time R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…69 Previous studies have shown that RA treatment activates fatty acid oxidation, leading to increased expression of Cpt1a expression. [70][71][72] Our analysis also revealed differences in the levels of various phospholipid species. These differences were seen in comparing LV versus RV and also in comparing the two genotypes, Rbp1 -/and WT mice.…”
Section: Carnitine and Lipid Biosynthetic Pathwaymentioning
confidence: 57%
See 1 more Smart Citation
“…69 Previous studies have shown that RA treatment activates fatty acid oxidation, leading to increased expression of Cpt1a expression. [70][71][72] Our analysis also revealed differences in the levels of various phospholipid species. These differences were seen in comparing LV versus RV and also in comparing the two genotypes, Rbp1 -/and WT mice.…”
Section: Carnitine and Lipid Biosynthetic Pathwaymentioning
confidence: 57%
“…CPT1A is an important biomarker of diet‐related metabolic alterations, 67,68 and has also been identified as a potential biomarker of heart disease detection 69 . Previous studies have shown that RA treatment activates fatty acid oxidation, leading to increased expression of Cpt1a expression 70–72 …”
Section: Discussionmentioning
confidence: 99%
“…Vimaleswaran et al's findings demonstrated that variations in the RXR gene, including VDR (22 tag SNPs) and RXRG (23 tag SNPs), did not provide strong evidence for interactions between allelic variations in VDR and RXRG genes on metabolic outcomes [20]. The relationship between RXRA polymorphisms and lipid and lipoprotein levels has been widely considered [7,[21][22][23]. In a study, Lima et al reported that polymorphisms in the RXRA gene (rs11381416) influence the triglycerides level in a Southern Brazilian population [7].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this Special Issue was to expand and add to the research which uses genomics technologies in the development of personalized nutrition recommendations. This Special Issue on “Genomics and Personalized Nutrition” features five original articles [ 5 , 6 , 7 , 8 , 9 ] and four reviews [ 10 , 11 , 12 , 13 ] which examine two facets of personalized nutrition: 1—genomics and food bioactive compounds; and 2—genetic variations and diet interactions.…”
mentioning
confidence: 99%
“…Overall, this study suggests that milt herring is a novel marine ingredient to help fight against metabolic syndrome. Secondly, Cifre et al, 2020 [ 6 ] show that the administration of all-trans retinoic acid regulates the expression of key inflammatory and lipid metabolism genes in an ex vivo system of peripheral blood mononuclear cells in normal-weight and overweight–obese subjects. These studies are excellent examples of the use of various genomics techniques to further understand the effects of foods on health and to adapt our current recommendations.…”
mentioning
confidence: 99%